A study of records management practices in Camp Karingal an assessment - Desuasido, Lenna Rosa P. (2006)
This study focuses on the records management system of Camp Karingal. For an organization as record-dependent and as data-intensive as the police, it is important to review, evaluate, and assess the current conditions of its recordkeeping practices. This study assesses and evaluates the effectivity and efficiency of Camp Karingal's records section and determine if Executive Order No.113, also known as PRESCRIBING THE RULES AND REGULATIONS FOR THE GOVERNMENT OF CITY AND MUNICIPAL POLICE AGENCIES THROUGHOUT THE PHILIPPINES from the Police Act of 1966, can be good framework in which to formulate a standard records management policy to be implemented in police stations and precincts nationwide. The study has established that the current conditions of the records of Camp Karingal when it comes to the creation, maintenance and use, and disposition of records is serviceable but not efficient most especially when it comes to information retrieval and records retention and disposition.